2010
DOI: 10.2174/138920210793175895
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA: Biogenesis, Function and Role in Cancer

Abstract: MicroRNAs are small, highly conserved non-coding RNA molecules involved in the regulation of gene expression. MicroRNAs are transcribed by RNA polymerases II and III, generating precursors that undergo a series of cleavage events to form mature microRNA. The conventional biogenesis pathway consists of two cleavage events, one nuclear and one cytoplasmic. However, alternative biogenesis pathways exist that differ in the number of cleavage events and enzymes responsible. How microRNA precursors are sorted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1,157
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,517 publications
(1,180 citation statements)
references
References 371 publications
(473 reference statements)
5
1,157
0
18
Order By: Relevance
“…An increasing number of studies have suggested that miRNAs are a class of small highly conserved molecules that perform a crucial role in the regulation of multiple cellular events including cellular proliferation, differentiation, development and apoptosis (8,20,21). Dysregulation and dysfunction of miRNAs leads to the initiation and development of cancers, indicating that miRNAs are important molecules that can potentially be used for the diagnosis and treatment of cancers (22).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have suggested that miRNAs are a class of small highly conserved molecules that perform a crucial role in the regulation of multiple cellular events including cellular proliferation, differentiation, development and apoptosis (8,20,21). Dysregulation and dysfunction of miRNAs leads to the initiation and development of cancers, indicating that miRNAs are important molecules that can potentially be used for the diagnosis and treatment of cancers (22).…”
Section: Discussionmentioning
confidence: 99%
“…The standard miRNA biogenesis pathway consists of two cleavage events, one nuclear and one cytoplasmic [21]. After the cleavage, primary miRNAs are processed into active mature miRNAs through a series of biochemical steps, and miRNA expression can be regulated at each step of biogenesis pathway (Fig.…”
Section: Mirna Biogenesis and Functionmentioning
confidence: 99%
“…The miRNAs can induce target mRNA degradation and translational repression through its recognition elements pairing to 3 0 -untranslated region (3 0 -UTR) of the target mRNAs [15,16]. Moreover, dysregulation of miRNA also has been observed in cancers including NSCLC [17,18]. Blower et al have studied the effect of miRNAs on chemotherapy and find that the expression patterns of miRNAs is significantly correlated with the potency patterns of 3089 chemical compounds [19].…”
Section: Introductionmentioning
confidence: 99%